تأثير بعض المتغيرات الديموغرافية في سلوك المستهلك عند شراء الأغذية المحفوظة في محافظة اللاذقية. - يعقوب, غسان; سلطانة, علي; علي, غيث أمين (Latakia University Journal -Biological Sciences Series, 2014)
هدفت الدراسة إلى تحديد أو معرفة تأثير بعض المتغيرات الديموغرافية على سلوك المستهلك عند شراء الأغذية المحفوظة في محافظة اللاذقية, واستخدم المنهج الوصفي التحليلي لدراسة مدى التأثير، وتم اختيار عينة مكونة من 210 مستهلك من مجتمع الدراسة في محافظة اللاذقية, موزعة على أربعة أحياء هي: الصليبة والزراعة وحي تشرين والرمل الشمالي, بالإضافة إلى ثلاث مناطق هي: الحفة وجبلة وريف منطقة اللاذقية, واستخدم استبيان احصائي. وبعد تحليل البيانات, أظهرت الدراسة أنه لا يوجد تأثير لمستوى تعلم المستهلك في سلوكه الشرائي بالنسبة لأنواع العبوات, في حين يوجد تأثير لمستوى تعلم المستهلك في سلوكه الشرائي لوجود المواد الحافظة في الأغذية المحفوظة, كما يوجد تأثير لعنوان السكن في السلوك الشرائي للمستهلك بالنسبة لطريقة حفظ الأغذية, كذلك يوجد تأثير لدخل المستهلك في سلوكه الشرائي بالنسبة لما يهمه عند الشراء (السعر, الجودة, أو الاسم التجاري) وكذلك بالنسبة لمكان التسوق. وقد بيّنت نتائج البحث, أن 42.4% من أفراد عينة البحث يفضلون حفظ الأغذية بطريقة التجميد, ونحو 64.3% من المستهلكين يدققون على وجود المواد الحافظة عند شراء الأغذية. نتيجة لاهتمامهم بالناحية الصحية, فإن نحو 63.3% يفضلون العبوات الزجاجية على غيرها من العبوات. كذلك نلاحظ أن 46.7% من عينة الدراسة يهتمون بجودة المنتج عن غيره من الاهتمامات عند شراء الأغذية. كما بيّنت النتائج أن نحو 79% من عيّنة الدراسة, لا يتجاوز إنفاقهم الشهري على شراء الأغذية المحفوظة (5000) ل.س, وأن نحو 45% من عينة الدراسة نسبة إنفاقهم الشهري على شراء الأغذية المحفوظة تتراوح بين (10-20%) من مجمل الإنفاق على شراء الأغذية, وما نسبته (5-10%) من الدخل الشهري. This study aimed to identify or learn some of the demographic variables and their impact on consumer behavior, when buying preserved food in the governorate of Latakia; using descriptive analytical study of the impact. The sample of 210 consumer was selected from among the study society in Lattakia, spread over four districts namely: Saliba, Al Ziraa, Tishreen ave and north sand, in addition to the three regions of: Al-Haffah, jableh and Lattakia rural area; a questionnaire was used across the sample. Analysis of the data showed that the consumer level of education has no impact on his buying behaviour regarding packaging, whereas there as an impact of the consumer level of education on his buying behaviour for the presence of preservatives in preserved food, and there is an impact of home address on consumer buying behaviour for keeping preserved food, there is also an effect of the consumer income on his buying behaviour regarding the interests at the time of purchase (price, quality, or trade name), as well as for the marketplace. Research results showed that 42.4% sample members prefer food preservation by freezing method, about 64.3% consumers checked on presence of preservatives when buying food. As a result of their interest in terms of health, some 63.3% prefer glass containers over other packaging. Also note that the study sample of 46.7% care about product quality from other concerns when buying food. Also, the results showed that about 79% of the study sample, do not exceed 5000 SP for the monthly spending on the preserved food, And nearly 45% of monthly spending on preserved foods is ranging from (10-20%) of the total expenditure on the purchase of food, and of (5-10%) of the monthly income.